A renal transplant patient with COVID-19 presented with acute cellular rejection - Neda Soleimani; Sahand Mohammadzadeh (Society of Diabetic Nephropathy Prevention, 2023)
A 27-year-old man underwent a deceased kidney transplant. Three days after transplantation, COVID-19 was diagnosed for our patient. Immunosuppressants were reduced and a renal biopsy was conducted, which showed acute T cell-mediated rejection. We intened to share a case to help clinicians to understand the risks that kidney transplant recipients face.